KTCNlncDB—a first platform to investigate lncRNAs expressed in human keratoconus and non-keratoconus corneas - Szcześniak, Michał W. (Database (Oxford), 2017)
Keratoconus (KTCN, OMIM 148300) is a degenerative eye disorder characterized by progressive stromal thinning that leads to a conical shape of the cornea, resulting in optical aberrations and even loss of visual function. The biochemical background of the disease is poorly understood, which motivated us to perform RNA-Seq experiment, aimed at better characterizing the KTCN transcriptome and identification of long non-coding RNAs (lncRNAs) that might be involved in KTCN etiology. The in silico functional studies based on predicted lncRNA:RNA base-pairings led us to recognition of a number of lncRNAs possibly regulating genes with known or plausible links to KTCN. The lncRNA sequences and data regarding their predicted functions in controlling the RNA processing and stability are available for browse, search and download in KTCNlncDB (http://rhesus.amu.edu.pl/KTCNlncDB/), the first online platform devoted to KTCN transcriptome. Database URL: http://rhesus.amu.edu.pl/KTCNlncDB/